2010
DOI: 10.5191/jiaee.2010.17106
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Global Mindedness of Extension Agents: Implications for Building Global Awareness of Extension Agents

Abstract: Because of the profound effect that globalization has on our society the Cooperative Extension Service of the United States has been challenged to develop programs that help people deal with these changes. The purpose of this study was to determine the level of global mindedness among Extension agents in North Carolina and to identify the factors affecting their global mindedness. This study found that the typical Extension agent from North Carolina has a moderate to high level of global mindedness on this sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…International experiences have been shown to positively impact learning. Smith, Jayaratne, Moore, Kistler, and Smith (2010) found extension professionals with international experience were significantly more likely to have a global mindset. "A new appreciation for extension's role in international development" (Place et al, 2008, p. 8) was reported by extension professionals as a direct result of their firsthand international experience in Latin America.…”
Section: Introduction and Theoretical/conceptualmentioning
confidence: 99%
See 1 more Smart Citation
“…International experiences have been shown to positively impact learning. Smith, Jayaratne, Moore, Kistler, and Smith (2010) found extension professionals with international experience were significantly more likely to have a global mindset. "A new appreciation for extension's role in international development" (Place et al, 2008, p. 8) was reported by extension professionals as a direct result of their firsthand international experience in Latin America.…”
Section: Introduction and Theoretical/conceptualmentioning
confidence: 99%
“…Due to a need to keep time away from home at a minimum, short-term international experiences are becoming more common (Festervand & Tillery, 2001;Paus & Robinson, 2008). Despite these challenges, extension systems around the world are expressing a need for the globalization of national agricultural extension systems (Qamar, 2002) and a trend towards international experiences can be noticed across the globe (Smith et al, 2010).…”
Section: Introduction and Theoretical/conceptualmentioning
confidence: 99%
“…Further research should be conducted on common teaching practices of secondary, post-secondary, and extension agricultural education programs abroad, as well as on determining methods through which educators can build their ability to evaluate and understand international contexts. Research reflects an agreeance on the importance of globalizing American curriculum in both secondary, post-secondary, and extension settings (e.g., Ludwig, 1994;Martin & Elbasher, 1994;Smith et al, 2010). However, none of the research articles identified in this synthesis evaluated how global competencies were being included in secondary, post-secondary, or extension settings, nor did any of the articles address the effectiveness of the globalization of American agriculture curriculum.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Mertens and Wilson (2018) expressed the necessity of evaluating something that was implemented on a particular period of time to determine its value and worth. Alkin and Christie (2004) declared it is imperative to identify the areas of concern in evaluating a project and to choose an appropriate method in collecting and analyzing data for sound decisions to be made (Ruggles et al, 2010;D. B. Smith, Moore, Jayaratne, Kistler, & Smith, 2009) also affirmed that the use of evaluation is imperativefor community extension projects offered by schools to its community partners in order to measure the effectiveness, outcomes, and impact of the services offered to the people.…”
Section: Theoretical Lensmentioning
confidence: 99%